PD-1 and PDL-1 Immune Checkpoint Inhibitors: Emerging Hope for the Future of Lung Cancer Immunotherapy - Ilyasa, Muhammad Riza; Ramadhani, Muhammad Zulmi; Santoso, Rex Jeremy; Hutasoit, Gina Andyka; Miskad, Upik Anderiani (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Lung cancer is the leading cause of cancer-related deaths worldwide, with Non-Small Cell Lung Cancer (NSCLC) being the most common type. Despite advances in treatment, the prognosis remains poor. Immune checkpoint inhibitors targeting PD-1 and PD-L1 have emerged as a promising first-line treatment approach in combating cancer. Objectives: This literature review aims to evaluate the effectiveness of PD-1 and PD-L1 immune checkpoint inhibitors in the treatment of NSCLC. It also explores the potential of these inhibitors to improve patient survival rates compared to conventional therapies. Methods: A systematic literature search was conducted using databases such as PubMed, Google Scholar, ScienceDirect, and NCBI, with keywords including